TYR Gene in Llamas: Polymorphisms and Expression Study in Different Color Phenotypes - Anello, Melina; Fernández, Estefanía; Daverio, María Silvana; Vidal-Rioja, Lidia; Di Rocco, Florencia (Frontiers in Genetics, 2019)
Tyrosinase, encoded by TYR gene, is an enzyme that plays a major role in mammalian pigmentation. It catalyzes the oxidation of DOPA to DOPAquinone, a precursor of both types of melanin: eumelanin and pheomelanin. TYR is commonly known as the albino locus since mutations in this gene results in albinism in several species. However, many other TYR mutations have been found to cause diluted phenotypes, like the Himalayan or chinchilla phenotypes in mice. The llama (Lama glama) presents a wide variety of coat colors ranging from non-diluted phenotypes (eumelanic and pheomelanic), through different degrees of dilution, to white. To investigate the possible contribution of TYR gene to coat color variation in llamas, we sequenced TYR exons and their flanking regions and genotyped animals with diluted, non-diluted and white coat, including three blue-eyed white individuals. Moreover, we analyzed mRNA expression levels in skin biopsies by qPCR. TYR coding region presented 9 SNPs, of which 3 were non-synonymous, c.428A>G, c.859G>T and c.1490G>T. We also identified seven polymorphisms in non-coding regions, including two microsatellites, an homopolymeric repeat, and five SNPs: one in the promoter region (c.1-26C>T), two in the 3’UTR and two flanking the exons. Only c.1-26C>T presented association with diluted phenotypes, though not complete. Results from qPCR showed that expression levels of TYR in white llamas were significantly lower (p<0.05) than those in diluted and non-diluted phenotypes. Screening for variation in regulatory regions of TYR did not reveal polymorphisms that explain such differences. However, data from this study showed that TYR expression levels play a role in llama pigmentation.